An invariant-based elasto-visco-plastic model for unidirectional polymer composites at finite strains. (1st February 2022) - Rodrigues Lopes, Igor A.; Camanho, Pedro P.; Andrade Pires, Francisco M.; Arteiro, Albertino
Abstract: An invariant-based constitutive model for unidirectional composites, including viscous effects in the elastic and plastic regimes at finite strains, is proposed. The model is based on the multiplicative decomposition of the deformation gradient, using an isoclinic configuration to avoid the non-uniqueness of intermediate configurations. The visco-elastic behaviour is represented by the generalised Maxwell model, combined with a transversely isotropic yield function and a non-associative plastic potential. Visco-plastic effects are introduced through the Perzyna overstress function. The theoretical basis of the material model and the computational treatment within the finite element solution procedure are presented in detail. Two algorithms are proposed for an implicit integration of the evolution equations: (i) a semi-implicit stress update, and (ii) a fixed-point iterative fully implicit stress update. A comparison of their performance reveals that the former becomes faster, even though the latter guarantees the quadratic convergence rate in the Newton–Raphson scheme. The predicted stress–strain response for different fibre orientation angles is in close agreement with experimental data obtained under quasi-static and dynamic loading. The model can also capture the important re-orientation of the fibres due to external loading.